Laminação sob atmosfera controlada dos sistemas MgH2 e MgH2 - LaNi5 para armazenagem de hidrogênio - Coavas, Jose Jaime Marquez (Universidade Federal de São Carlos, 2016)
Magnesium hydride is a promisor candidate for H2 storage, manly due its high hydrogen gravimetric capacity (7.6% wt), low density, abundance and low cost. However, its H-absorption/desorption occurs only at temperatures around 673 K with slow kinetics. Moreover, Mg and MgH2 surfaces are highly reactive, easily forming MgO and/or Mg(OH)2 layers that lower the level the hydrogen storage properties. It described in the literature that the use the severe plastic deformation technique or the incorporation of additives such as LaNi5 improve the hydriding/dehydriding kinetics and lower the dehydrogenation temperature of Mg-based composites. In the present study, Mg-based hydrogen storage alloys has been developed in the following systems: MgH2 and MgH2 + LaNi5 using the cold rolling (CR) under inert atmosphere. The aspect analyzed in this study were the processing parameters (number of passes and roll rotation frequency) and the additive incorporation (LaNi5) during the processing and Habs / des behavior. The micro and nanoestrutural characterization for the obtained materials were made by means of X-ray diffraction (XRD), scanning a transmission electron microscopy (SEM and TEM), and the correlation of results obtained with the process route, showed that larger number of rolling passes and high frequency produces nanocomposites with great improvements in the hydrogen storage properties. Furthermore, was observed a catalytic effect with the addition of LaNi5 to MgH2, due the formation of new phases in hydriding/dehydriding process. The best result for hydrogen storage were obtained for the system MgH2+1,50 mol.% LaNi5 with low Habsorption / desorption temperatures, aspect interesting for MgH2.
Cold rolling under inert atmosphere of the system MgH2 and MgH2 - LaNi5 for hydrogen storage
Keywords: Laminação a frio; Atmosfera controlada; Parâmetros de processamento; Nanofases; Cold rolling; Protective atmosphere; Rolling parameters; Nanophases; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS